2002
DOI: 10.1089/107555302320825084
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization of Carmustine with Maitake β-Glucan on Androgen-Independent Prostatic Cancer Cells: Involvement of Glyoxalase I

Abstract: This study demonstrates a sensitized cytotoxic effect of BCNU with beta-glucan in PC-3 cells, which was associated with a drastic (approximately 80%) inactivation of Gly-I. Therefore, the BCNU/beta-glucan combination may help to improve current treatment efficacy by targeting Gly-I, which appears to be critically involved in prostate cancer viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…This group found that glucan administration increased suppression of tumor growth, apoptosis and antitumor response. Similar observations were found by others [14,15]. In different types of cancer, treatment with glucan and melatonin (individually or together) inhibited progression of adenocarcinoma [16].…”
Section: Discussionsupporting
confidence: 90%
“…This group found that glucan administration increased suppression of tumor growth, apoptosis and antitumor response. Similar observations were found by others [14,15]. In different types of cancer, treatment with glucan and melatonin (individually or together) inhibited progression of adenocarcinoma [16].…”
Section: Discussionsupporting
confidence: 90%
“…An acid-treated fraction (ATF) of Agaricus blazei extract directly inhibited tumor growth by inducing apoptotic processing in Balb/C mice (25). However, this result was later contradicted by another research study which demonstrated that ß-glucan from maitake mushrooms was only active for PC-3 cells in combination with carmustine (BCNU), an anticancer agent (27). ß-glucan obtained from maitake mushroom induced >90% cytotoxic cell death in PC-3 cells at 480 μg/ml in 24-h treatment (26).…”
Section: Discussionmentioning
confidence: 99%
“…10 A separate study also demonstrated a chemosensitizing effect of D-fraction, in which the cytotoxic effect of the anticancer agent carmustine, was significantly enhanced in combination with Dfraction, resulting in ~90-percent cell viability reduction (cell death). 11 These results suggest that the D-fraction may be an alternative treatment modality for prostate cancer and may also work cooperatively with ongoing chemotherapy.…”
Section: Maitake D-fractionmentioning
confidence: 89%